Employing Participatory Risk Mapping (PRM) as a land-use planning method: the case of a derelict former hospital in Laredo, Texas, USA. Issue 2 (4th March 2021) - Hilburn, Andrew; Zawisza, Thomas; Bazan, Julie; Cruz, Rey; Rodriguez, José
ABSTRACT: Participatory methods that are structured, equitably collected, and produce analysable data offer improvement to the often predetermined and hierarchical land-use planning process. Participatory Risk Mapping (PRM), was used to garner feedback on potential land uses and current concerns regarding an abandoned hospital property in Laredo, Texas, USA by interviewing 496 participants who live within view of the former hospital. Overall, PRM is an efficient and systematic approach to including key stakeholders into sustainable and equitable urban land-use planning.